Critical interculturality, transdisciplinarity and decoloniality in the formation of indigenous teachers of the Berò Biawa Mahadu / Javaé people: Analysis of pedagogical practices contextualized in a course of Indigenous Intercultural Education - Nazareno, Elias; De Magalhães, Sônia Maria [UNESP]; Freitas, Marco Túlio Urzeda (Fronteiras: Journal of Social, Technological and Environmental Science, 2019)
The undergraduate course Intercultural Education of the Universidade Federal de Goiás was created in 2007 and its fundamental objective is to provide higher education to indigenous teachers from 25 indigenous peoples that work in the schools of their territories in the Araguaia-Tocantins and Xingu region. The pedagogical principles of the course are the interculturality and the transdisciplinarity, which are thought out from a decolonial perspective and as potentializing concepts to the emergence of new epistemological bases that contribute to the construction of intercultural and interepistemic syllabuses for indigenous schools. This study seeks to perceive the possibilities for the emergence and affirmation of indigenous knowledge's through new contextualized pedagogical practices implemented by students from the people Javaé throughout their practicum period in the course Intercultural Education.
Interculturalidade Crítica, Transdisciplinaridade e Decolonialidade na Formação de Professores Indígenas do Povo Berò Biawa Mahadu/Javaé: Análise de Práticas Pedagógicas Contextualizadas em um Curso de Educação Intercultural Indígena
Keywords: Decoloniality; Epistemic Interculturality; Indigenous School Education